Leadless pacemaker implantation: An unexpected complication. Issue 2 (16th November 2021) - Berdaoui, Brahim; Pintea Bentea, Georgiana; Samyn, Sophie; Morissens, Marielle; Castro Rodriguez, Jose
Abstract: The leadless pacemaker is an emerging technology with high efficacy and reduced complications rates. However, due to its novel status, some pitfalls remain to be addressed. We report the case of a 91‐year‐old patient undergoing a Micra pacemaker implantation. During the procedure, the maneuvers required for the adequate deployment of the device led to damaging of the septal tricuspid leaflet, resulting in severe tricuspid regurgitation. This is a severe mechanical complication of the Micra implantation technique, not previously reported in literature. In light of the novelty of the leadless pacemaker, we should remain cautious with regards to potential unreported complications.